The Ngāruawāhia Tūrangawaewae Regatta: Today’s Reflections on the Past - Rewi, Tangiwai (Waka Kuaka, 2015)
The 118th Ngāruawāhia Tūrangawaewae Regatta was celebrated on the 16th of March 2013. First held on the 17th March 1896, it is the second oldest regatta in New Zealand behind the Auckland Regatta of the 1870s. Renowned for the majestic fleet of ornately carved waka taua 'war canoes' on parade, crowds still flock to Ngāruawāhia today to watch the waka taua make their annual salute to King Tuheitia, the 7th monarch of the Māori King Movement, and his dignitaries. This narrative details my journal observations of March 2013 from the Waikato River banks, before delving into historical information detailing the advent of the Regatta, the Māori King Movement's historical capital base and relocation, and the significance of these to Regatta. The next section speaks of the Waikato River connection, along with early Regatta features, and the promotion of kotahitanga 'embracing togetherness' within the Ngāruawāhia community, the Waikato Region and more generally across Aotearoa/New Zealand. The article concludes with a comparison of early Regatta and that of 2013.